1997
DOI: 10.1159/000268027
|View full text |Cite
|
Sign up to set email alerts
|

Photoreceptor Transplants Increase Host Cone Survival in the Retinal Degeneration (rd) Mouse

Abstract: Retinal transplants offer a potentially interesting approach to treating human retinal degenerations, but so far little quantitative data are available on possible beneficial effects. We isolated photoreceptor layers from normal-sighted mice and grafted them into the subretinal space of retinal degeneration (rd) mice lacking rod photoreceptors. At 2 weeks after surgery, the numbers of residual host cone photoreceptors outside the graft zone were quantified following specific labelling. Examination of operated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 18 publications
5
62
0
Order By: Relevance
“…The existence of diffusible trophic factors influencing photoreceptor survival initially was suggested from studies of chimeric normal and dystrophic rat retina in which regions of rod survival overgrew normal retinal pigmented epithelium (31). This hypothesis is supported by our recent findings (20) that transplantation of isolated outer nuclear layer fragments from C57BL͞6 mice (and hence 97% pure in rods) promote survival of cones in the rd host retina, including at distance from the transplantation site (20). Taken together, these studies support a role for cellular interactions in cone survival within dystrophic and possibly normal retina.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The existence of diffusible trophic factors influencing photoreceptor survival initially was suggested from studies of chimeric normal and dystrophic rat retina in which regions of rod survival overgrew normal retinal pigmented epithelium (31). This hypothesis is supported by our recent findings (20) that transplantation of isolated outer nuclear layer fragments from C57BL͞6 mice (and hence 97% pure in rods) promote survival of cones in the rd host retina, including at distance from the transplantation site (20). Taken together, these studies support a role for cellular interactions in cone survival within dystrophic and possibly normal retina.…”
Section: Discussionsupporting
confidence: 65%
“…This model appears appropriate to test the hypothesis of the dependence of cones on the viability of rods. Indeed, we found that transplantation of rod-rich photoreceptor transplants to these animals at an age when most rods have disappeared induced a significant increase in host cone survival (20).…”
mentioning
confidence: 85%
“…Although there is evidence that transplants themselves are functional (Adolph et al, 1994;Seiler et al, 1999) and that some degree of graft-host integration can occur after retinal transplantation (Ehinger et al, 1991;Silverman et al, 1992;Gouras et al, 1994;Aramant and Seiler, 1995;Seiler and Aramant, 1998;Ghosh et al, 1999;Kwan et al, 1999;Gouras and Tanabe, 2003;Zhang et al, 2003), the presence of definite functional synaptic connections has not yet been reported. As a second potential mechanism of action, the transplanted tissue could provide an indirect effect via the release of humoral factors that could prevent or retard the degeneration of the remaining host photoreceptors (Mohand-Said et al, 1997, 2000Fintz et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…First, the visual responses in the caudal SC were observed only in a very small area of the SC precisely corresponding to the placement of the graft in the retina. If a trophic effect of the transplant on host photoreceptors was the cause, it should have an effect on a larger retinal area, as has been observed in rd mice with rod photoreceptor transplants (Mohand-Said et al, 1997). Second, based on S-antigen immunoreactivity, no difference was observed in the number of remaining cone photoreceptors near the transplant site and other areas of the host retina.…”
Section: Mechanism Underlying the Visual Restorationmentioning
confidence: 91%